Morphological study and DNA fingerprint pattern of Goniothalamus tapis and G. umbrosus (Annonaceae) using M13 marker and its taxonomic implication - IMAM MAHADI; FATHURRAHMAN FATHURRAHMAN; NERY SOFIYANTI; AGUS SUSATYA (Society for Indonesian Biodiversity, 2023)
Abstract. Mahadi I, Fathurrahman F, Sofiyanti N, Susatya A. 2023. Morphological study and DNA fingerprint pattern of Goniothalamus tapis and G. umbrosus (Annonaceae) using M13 marker and its taxonomic implication. Biodiversitas 24: 6299-6306. The species of Goniothalamus (Blume) JD Hooker & Thomson (Annonaceae) is widely considered a source of traditional medicine and containsoniothalamin, which is used for anti-cancer and anti-bacterial drugs. Goniothalamus tapis and G. umbrosus are traditional medicines in Sumatra, Indonesia, and Malaysia Peninsula, respectively. The community uses this plant as a source of traditional medicinal ingredients. Clinically, Goniothalamus contains the compound goniothalamin, an anti-cancer and anti-bacterial drug. The existence of this plant is gradually maintained. G. tapis is often used as a traditional medicine for the Malay community in Sumatra, and G. umbrosus is widely used by the Malay community in the Peninsular Malaysia. These two plants are morphologically similar, but the two species are different. Some researchers consider these plants to be the same. For this reason, it needs to be studied by combining two methods, both molecular and morphological. G. tapis and G. umbrosus are species of the Goniothalamus distributed in Sumatra and Peninsular Malaysia. Their taxonomic status needs to be clarified due to the morphological character similarity. This study aimed to study the morphological characters of G. tapis and G. umbrosus as well as their DNA fingerprint pattern using M13 Marker. The morphological examination showed that G. tapis and G. umbrosus characters are distinguished by leaf, flower, and fruit. This result is supported by a DNA fingerprint pattern using an M13 marker. The results show that these two species are different both in terms of morphology and fingerprints. So, it can be concluded that these two species are different.